2022
DOI: 10.3390/ma15072445
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Tensile Model of Hemp-Fiber-Reinforced Poly(butylene adipate-co-terephthalate) Composite

Abstract: The preparation of a high-strength biodegradable plastic has always been the focus of academia. Here, we prepared two biodegradable composites using silane coupling-agent-modified hemp fibers (Si-HF) and unmodified hemp fibers (HF) with butylene adipate-co-terephthalate (PBAT), respectively. We compared the differences of Si-HF/PBAT and HF/PBAT in terms of micromorphology, density, mechanical properties, thermal stability and biodegradability. The Si-HF has better interface interaction between the hemp and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…PBAT can be added with micro-crystalline cellulose (MCC) with coffee husk (CH) and rice husk (RH) with hemp fibre (HF) or grape pomace (GP) [103,104]. When the filler is added without a compatibiliser, smaller quantities can be used (for example, up to 20% by weight in the case of MCC) because, beyond this threshold, the presence of the filler can create cracks in the interface matrix of the fibre, which propagate premature fracturing of the the materials [105].…”
Section: Use Of Agri-food Waste As Fillermentioning
confidence: 99%
“…PBAT can be added with micro-crystalline cellulose (MCC) with coffee husk (CH) and rice husk (RH) with hemp fibre (HF) or grape pomace (GP) [103,104]. When the filler is added without a compatibiliser, smaller quantities can be used (for example, up to 20% by weight in the case of MCC) because, beyond this threshold, the presence of the filler can create cracks in the interface matrix of the fibre, which propagate premature fracturing of the the materials [105].…”
Section: Use Of Agri-food Waste As Fillermentioning
confidence: 99%
“…However, the introduction of moringa seed powder reduced the crystallinity of PBAT, resulting in increased permeability rates for gases and water vapor. In addition, Zeng et al 20 prepared two biodegradable composites using silane coupling agent‐modified hemp fibers (Si‐HF) and unmodified hemp fibers (HF) as raw materials. The interfacial interaction between Si‐HF and PBAT matrix is better than that of HF, thus improving the tensile properties of Si‐HF/PBAT.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Zeng et al confirmed the favorable biodegradability of hemp fiber/PBAT composites through soil burial degradation tests. Since most natural plant fibers have high water absorption and wettability, they can promote the degradation of composites [17]. As a result, the degradation rate of PBAT composites can be significantly accelerated.…”
Section: Introductionmentioning
confidence: 99%